2010
DOI: 10.1002/chem.201000369
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Biologically Interesting 3,4‐Diaryl‐Substituted Succinimides and Maleimides: Application of Iron‐Catalyzed Carbonylations

Abstract: A straightforward two-step synthesis of trans-3,4-disubstituted succinimides through a palladium-catalyzed Sonogashira reaction and an iron-catalyzed double carbonylation is described. In situ oxidative dehydrogenation gave the corresponding 3,4-diarylmaleimides. By starting from readily available aryl and heteroaryl halides, a variety of new analogues and derivatives of bioactive 3,4-bisindolylmaleimides are obtained in good yield and selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 149 publications
0
19
0
Order By: Relevance
“…Beller's group reported an one‐pot method for the synthesis of various substituted succinimides 223 by means of [Fe(CO) 5 ] or [Fe 3 (CO) 12 ] catalyzed double carbonylation of alkynes and nucleophilic attack (both in intermolecular and intramolecular manners) starting from different terminal and internal alkynes 222 with ammonia or amines in 2009 (Scheme 34). [51] Later, potentially bioactive 3,4‐diaryl‐substituted succinimdes and maleimides were also synthesized [52] . Furthermore, this iron‐catalyzed carbonylation strategy was used as a key step in the short and efficient synthesis of Himanimide A and B [53] …”
Section: Iron‐catalyzed Synthesis Of Pyrrolidinonesmentioning
confidence: 99%
“…Beller's group reported an one‐pot method for the synthesis of various substituted succinimides 223 by means of [Fe(CO) 5 ] or [Fe 3 (CO) 12 ] catalyzed double carbonylation of alkynes and nucleophilic attack (both in intermolecular and intramolecular manners) starting from different terminal and internal alkynes 222 with ammonia or amines in 2009 (Scheme 34). [51] Later, potentially bioactive 3,4‐diaryl‐substituted succinimdes and maleimides were also synthesized [52] . Furthermore, this iron‐catalyzed carbonylation strategy was used as a key step in the short and efficient synthesis of Himanimide A and B [53] …”
Section: Iron‐catalyzed Synthesis Of Pyrrolidinonesmentioning
confidence: 99%
“…Bisindolylmaleimides have been isolated from natural products (Kamata et al, 2006). The synthesis of bisindolylmaleimides (Prateeptongkum et al, 2010) and an example of a related crystal structure (Huang et al, 2012) have been reported.…”
Section: Data Collectionmentioning
confidence: 99%
“…The synthesis and functionalization of indoles have been the object of research for over one and a half century (Shiri, 2012). Few examples of Sonogashira-type reactions on the indole core have been described (Hussain et al, 2011;Prateeptongkum et al, 2010).…”
Section: D-mentioning
confidence: 99%